Estate duty wealth estimates and mortality multiplier - Lyons, P.M. (Economic & Social Studies, 1975)
Mortality multipliers are used in conjunction with estate duty data in many countries to estimate wealth distribution. Among the possible deficiencies of this approach is the fact that the estimates are dependent on the mortality multipliers which are used. This is a serious problem in the case of Irish wealth estimates, since mortality multipliers for the general population only were available, whereas multipliers for the upper socio-economic groups were used elsewhere. Accordingly, some adjusted sets o f mortality data from the UK were applied to the Irish estate duty data. Very different total amounts of personal wealth emerge from the various calculations, but the distributions are not at variance with some important earlier findings. These are that, notably, there is inequality in the distribution of wealth, with the top 5 per cent of adults owning over 60 per cent of wealth, males own at least two-thirds of that wealth, and mean wealth-holding increases with age, reaching a maximum in the 55 to 64 years age group.
Keywords: Economics; Sociology